SVM Based Reduction of Input Current Harmonics in Three Phase Rectifier. Issue 1 (September 2020) - Kesavan, T.; Sheebarani Gnanamalar, S.; Sivaranjani, S.; Gomathy, V.; Radhakrishnan, G.; Sitharthan, R.
Abstract: Current Scenario of power system engineering field is facing problem of harmonics in voltage and current. In power converter harmonics are mainly disturb the stability of voltage and current in uncertainty of load and transient. This paper proposes space vector modulation based analysis of input current in 3 phase converter. Harmonics in input current in converter is a big challenge of power Electronics research. In power converters non-linear load are one of the reason for increasing the harmonics in electronic circuits. Modified space vector modulation is proposed for reducing the harmonics in 3 phase converter and also control the total harmonic distortion. Matlab simulink software is used to simulate and analyse the 3 phase converter and SVM is modelled for above converter. In this propose method THD of input current harmonics has reduced below 5 percentages and compared with IEEE standard.